Epidemiological Features of Clostridium difficile Colonizing the Intestine of Jordanian Infants - Abu-Khader, Eman N.; Shehabi, Asem A.; Badran, Eman F. (International journal of microbiology, 2017)
Clostridium difficile is commonly found in the intestine of infants without causing any disease. This study investigated the most important epidemiological features of C. difficile strains colonizing intestine of Jordanian infants. A total of 287 fecal samples were collected from infants admitted to the Jordan University Hospital (JUH) over the period of 2015. Samples were cultured for C. difficile and their growth was identified using microbiological culture and PCR. The overall C. difficile colonization rate among hospitalized and nonhospitalized infants was 37/287 (12.9%). Neonates were less colonized than other infants (8.7% verses 19.5%). Colonization of the infants with C. difficile toxigenic strains (TcdA and TcdB) was observed in 54% of the isolates, whereas those colonized with nontoxigenic strains were 46% and only one isolate was positive for binary toxin. Breast feeding of infants is a significant factor associated with decreased colonization with C. difficile. All C. difficile strains were susceptible to vancomycin and metronidazole, while high resistance rate to ciprofloxacin (78.4%) and less resistance rate to erythromycin (29.7%) were detected among the isolates. The results showed that 40.5% of the isolates carried mutated gyrA and gyrB genes which have cross-resistance to ciprofloxacin and moxifloxacin. This study represents useful epidemiological features about C. difficile colonizing intestine of infants living in a developing country.